SKEMA AKTANSIAL DALAM WAYANG ORANG BERBAHASA ARAB: LESMANA MANDRAKUMARA (KAJIAN SEMIOTIKA NARATIF A. J. GREIMAS) - M Ulul Azmi; Dendi Yuda S; Rohanda Rohanda (Ihya al-Arabiyah: Jurnal Pendidikan Bahasa dan Sastra Arab, 2024)
Arabic-language wayang orang is a unique form of traditional art adaptation, but academic studies of the narrative structure of this performance are still relatively limited. This study aims to reveal and compare the narrative structures in two Arabic-language wayang orang performance programs through A.J. Greimas' narrative semiotics approach, focusing on the actantial schema that maps the relationships between roles in the storyline. The research method used is descriptive-analytical, with data collection techniques in the form of watching and listening to performance videos, which are then analyzed through the identification of actants such as the sender, subject, object, helper, opponent, and receiver. The results show that the use of Arabic does not change the foundations of Javanese tradition, but forms a more varied storytelling pattern through differences in the relationships between the actants in the two programs. A comparison of the two shows variations in the characters' goals, the intensity of the conflict, and shifts in actantial tension, which produce different narrative nuances even though the objects of their search are similar. Moral and social values are displayed through the characters' journeys and the dynamics of conflict, thus forming a symbolic narrative that remains rooted in the characters of wayang orang. These findings indicate that the adaptation of Arabic creates a hybrid narrative form that enriches the interpretation and meaning of traditional performing arts. The results are expected to serve as an analytical basis for studies.